Effect of dolomite amendment of acid Andosols on the performance of two green beans varieties in the Cameroon Western Highlands - Tamfuh P, Azinwi; Pangop CR, Kamga; Tapindje DG, Douanla; A, Boukong; FO, Tabi; F, Cho-Ngwa; D, Bitom (International Journal of Advanced Geosciences, 2019)
Soil acidity is a major factor limiting green beans (Phaseolus vulgaris L.) production in the Cameroon western Highland. A field experiment (split-plot layout) was conducted with seven dolomite treatments (tons ha-1): control or T0 (0), T1 (0.5), T2 (1), T3 (1.5), T4 (2), T5 (2.5) and T6 (3). Soil physico-chemical properties were determined meanwhile growth and yield parameters were collected weekly for a month and analyzed statistically. Results revealed that control soils were texturally silty sandy. The exchangeable bases (except Na), cation exchange capacity (CEC), base saturation and available phosphorus were very high. They acidity was moderate to high (5.2 to 5.6) while organic matter was very high (% dry mass) and of moderate to good quality (11<C/N ratio<13). Crop variety showed a highly significant difference (P<0.001) for all growth and yield parameters, with Cogito producing the longest (13.88 cm), most numerous (40.94 pods per plant) and highest (16.96 tons ha-1) extrafine pods. Dolomite doses revealed no significant effects (P>0.05) on crop parameters, although highest yield (13.61 tons ha-1) of extrafine pods came from 2 tons ha-1. The dolomite dose versus variety interaction showed no significant difference (P>0.05). Farmers ought to improve soils with compost and cover crops to check nutrient leaching and erosion.Â Â Â